Are YouTube Videos Useful in Informing Patients about Keratoplasty?. (3rd October 2021) - Kalayci, Mustafa; Cetinkaya, Ersan; Suren, Elcin; Yigit, Kenan; Erol, Muhammet Kazim
ABSTRACT: Purpose : The objective of this study was to analyze the quality of videos on YouTube as educational resources about keratoplasty surgery. Methods : The first 100 videos found after the keyword "keratoplasty for patients" was used in the YouTube search engine were included in the study. General video assessment included duration, views, likes, dislikes, and comments. The quality and accuracy of the information were evaluated by 2 independent ophthalmologists using DISCERN score, Journal of the American Medical Association (JAMA) score, global quality score and usefulness scoring system. Interobserver agreement and individual correlations of the data of each video were statistically analyzed. Results : Eighty-four of the first 100 videos met the inclusion criteria. The mean DISCERN score was 42.11, the mean JAMA score was 1.82, the mean global quality score was 2.35, and the mean usefulness score was 2.01. Twenty-eight (33.3%) of the surgical procedures described in the videos were penetrating keratoplasty, 18 (21.4%) were DMEK, 13 (15.5%) were DALK, four (4.8%) were DSAEK, and one (1.2%) was keratoprosthesis, while the remaining 20 (23.8%) videos did not mention any surgical procedure. Of the 84 videos, 26 (31%) had been uploaded by physicians, 46 (54.8%) by university/private health institutions, 11 (13.1%) by health channels, and one (1.2%) by a patient. Conclusion : YouTube is an important platform that can be used by patients to acquire information about keratoplasty. Increasing the number of uploads of informative keratoplasty videos by healthcare professionals will provide higher quality, more reliable, and more instructive content in this area.